PERANAN GREEN SOCIAL WORKERS PADA PROGRAM KAMPUNG IKLIM DI WILAYAH PESISIR INDONESIA - Ramdani, Jaka; Gunawan, Budhi; Darwis, Rudi Saprudin (Social Welfare Study Program, 2022)
Abstract. Climate change currently threatens 60 percent of Indonesia's total population residing in coastal areas at risk of land inundation due to sea level rise. Based on IPCC predictions, the coastal area of Ujungalang Village, Cilacap Regency, Central Java Province, will be affected. Efforts to increase adaptation to the impacts of climate change through the Climate Village Program are an alternative to minimize impacts. Uniquely, the empowerment program refers to Green Social Work which involves multi-parties such as Green Social Workers, Professions or experts (transdisciplinary), communities, and partnerships. Therefore, through this research, the role of Green Social Work in the Climate Village Program can be explored with a case study in Ujungalang Village, Cilacap Regency. The role of Green Social Workers is presented using qualitative data sourced from primary and secondary data. The in-depth interview process, semi-participant observations, and literature studies obtained research findings that Green Social Workers in the Climate Village Program played roles as Co-producers, Dialogue agents, Lobbyists, Coordinators, Translators, Curriculum changers, Mobilisers, screenwriters, Protectors, Consciousness-raisers. Through the role carried out by Green Social Workers in the Climate Village Program, it shows the success of a sustainable program for the people of Ujungalang Village. Keywords: Climate Village, Green Social Workers, Role. Abstrak. Perubahan iklim saat ini mengancam 60 persen dari total penduduk Indonesia yang bertempat tinggal di wilayah pesisir risiko tergenangnya daratan akibat kenaikan muka air laut. Berdasarkan prediksi IPCC wilayah pesisir Desa Ujungalang Kabupaten Cilacap Provinsi Jawa Tengah akan terkena dampaknya. Upaya peningkatan adaptasi dampak perubahan iklim melalui Program Kampung Iklim menjadi alternatif meminimalisir dampak. Uniknya program pemberdayaan tersebut merujuk pada Green Social Work yang melibatkan multi pihak seperti Green Social Worker, Profesi atau ahli (transdisiplin), masyarakat, dan kemitraan. Oleh karenanya, melalui penelitian ini dapat tereksplorasi peranan Green Social Work pada Program Kampung Iklim dengan studi kasus di Desa Ujungalang Kabupaten Cilacap. Peranan Green Social Worker disajikan menggunakan data kualitatif yang bersumber dari data primer maupun sekunder. Proses wawancara mendalam, observasi semi partisipan, dan studi kepustakaan memperoleh temuan penelitian bahwa Green Social Worker di Program Kampung iklim berperan sebagai Co-producers, Dialogue agents, Lobbyists, Coordinator, Translators, Curriculum changers, Mobilisers, pembuat skenario, Protectors, Consciousness-raisers. Melalui peranan yang dilakukan oleh Green Social Worker di Program Kampung Iklim menunjukan keberhasilan program yang berkelanjutan bagi masyarakat Desa Ujungalang. Kata kunci: Peranan, Green Social Workers, Kampung Iklim.